Electrical spin injection and detection in an InAs quantum well - Koo, Hyun Cheol; Yi, Hyunjung; Ko, Jae-Beom; Chang, Joonyeon; Han, Suk-Hee; Jung, Donghwa; Huh, Seon-Gu; Eom, Jonghwa (AMER INST PHYSICS, 2007)
The authors demonstrate fully electrical detection of spin injection in InAs quantum wells. A spin-polarized current is injected from a Ni81Fe19 thin film to a two-dimensional electron gas (2DEG) made of InAs based epitaxial multilayers. Injected spins accumulate and diffuse out in the 2DEG, and the spins are electrically detected by a neighboring Ni81Fe19 electrode. The observed spin diffusion length is 1.8 mu m at 20 K. The injected spin polarization across the Ni81Fe19/InAs interface is 1.9% at 20 K and remains at 1.4% even at room temperature. Their experimental results will contribute significantly to the realization of a practical spin field effect transistor.